2019
DOI: 10.3324/haematol.2019.219790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of donor lymphocyte infusion from an HLA-haploidentical donor: consensus recommendations from the Acute Leukemia Working Party of the EBMT

Abstract: onor lymphocyte infusion has been used in the management of relapsed hematologic malignancies after allogeneic hematopoietic cell transplantation. It can eradicate minimal residual disease or be used to rescue a hematologic relapse, being able to induce durable remissions in a subset of patients. With the increased use of haploidentical ABSTRACT B. Dholaria et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 98 publications
0
41
0
Order By: Relevance
“…In the context of a prophylactic or pre-emptive strategy, a few small studies comparing T-repleted haploidentical or HLA-identical DLIs in refractory or very high-risk AML observed higher rates of acute GVHD and NRM ( 24 , 25 ), while a large recent prospective study including 189 AL patients in first complete remission reported a prolonged graft and relapse-free survival after haploidentical HCT with an homogeneous ATG-based prophylaxis followed by DLI in comparison with HCT from matched related donors ( 26 ). Clinical trials are needed to establish the optimal timing and cell dose in both therapeutic and prophylactic settings after haploidentical HCT and the relationship with GVHD and disease response ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of a prophylactic or pre-emptive strategy, a few small studies comparing T-repleted haploidentical or HLA-identical DLIs in refractory or very high-risk AML observed higher rates of acute GVHD and NRM ( 24 , 25 ), while a large recent prospective study including 189 AL patients in first complete remission reported a prolonged graft and relapse-free survival after haploidentical HCT with an homogeneous ATG-based prophylaxis followed by DLI in comparison with HCT from matched related donors ( 26 ). Clinical trials are needed to establish the optimal timing and cell dose in both therapeutic and prophylactic settings after haploidentical HCT and the relationship with GVHD and disease response ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with relapsed/refractory Hodgkin disease, HAPLO transplantation has been credited for offering the most potent antitumor effect . The EBMT ALWP has recently proposed consensus recommendations for clinical applications of donor lymphocyte infusions from HAPLO donors and has recommended its use as safe and effective in patients in relapse or who still have detectable MRD and/or mixed donor chimerism after a HAPLO transplantation . For many teams, HAPLO donors are becoming the first choice when an alternative donor is sought.…”
Section: Discussionmentioning
confidence: 99%
“…25,44 The EBMT ALWP has recently proposed consensus recommendations for clinical applications of donor lymphocyte infusions from HAPLO donors and has recommended its use as safe and effective in patients in relapse or who still have detectable MRD and/or mixed donor chimerism after a HAPLO transplantation. 45 For many teams, HAPLO donors are becoming the first choice when an alternative donor is sought. The question whether a HAPLO donor might produce outcomes similar to those produced by genoidentical donors has recently been investigated retrospectively by the EBMT in a matched-pair analysis of 2654 adult patients with intermediate-risk and high-risk leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Donors were no longer a problem for most EMS patients [20,21]. Patients with high-risk myeloid malignancies may benefit from a prophylactic haplo-DLI, which should ideally be used in the setting of a clinical trial [22].…”
Section: Discussionmentioning
confidence: 99%